Genetic Analysis of Shade Tolerance in Chilli (Capsicum spp.) - Sreelathakumary I (Department of Olericulture, College of Agriculture, 2000)
Investigation on 'Genetic analysis of shade tolerance in chilli (Capsicum spp.)' was carried out in the Department ofOlericulture, College of Agriculture, Vellayani, during 1997 - 2000 with the objective of identifying superior genotype(s) of chilli to yield better under shade and to analyse the physiological, anatomical, biochemical and genetic basis of shade tolerance. Seventy genotypes of chilli belonging to C. annuum, C. Jrutescens and C. chinense collected from different parts of the country were initially evaluated under 25, 50 and 75 per cent shade in comparison with open condition for shade tolerance and yield. Plant height, internodal length, stem girth, leaf area, petiole length, days to first flower, node to first flower, height of node to first flower, fruits per plant, fruit length, fruit girth, fruit weight, yield and incidence of mite were found significantly different both among the genotypes and between different shade levels. High heritability combined with high GCV and expected genetic advance was observed for fruits per plant, fruit weight, fruit length, fruit girth, leaf area and yield under shade indicating the possibility of improvement of these characters through selection. A positive correlation was observed for fruits per plant, fruit length and fruit weight with yield at genotypic and phenotypic levels.